Hubungan Antaragama dalam Bidang Pendidikan, Perkawinan, Penguburan Jenazah, dan Upacara Hari-Hari Besar Keagamaan - Anis Masduqi (Al-Riwayah : Jurnal Kependidikan, 2017)
Interfaith relation is an important issue in the education field. Perhaps, it is because education plays a crucial role in the transfer of the science of religion and theology custody. Then religious education became a central issue in the arena of interreligious relations. Education will determine the style of interfaith relations in a plural society. Legislation on religious education thus should be criticized. The plurality of religion becomes a source of instability and disintegration seems to make the government tried to cope with any vulnerability harmony. Finally, the government issued regulations related to this issue. One of them is the Minister of Religious Affairs Decree Number 84 Year 1996 regarding Implementation Guidelines for Vulnerability Reduction Religious Harmony of Life. The operational guidelines vulnerability religious harmony is intended as a guide to the work of the officials and leaders of organizational units within the Ministry of Religious Affairs (now the Ministry of Religious Affairs) to take measures and coordinate in preventing insecurity in the field of religious harmony. Under these regulations, the causes of insecurity interreligious harmony, among others: the establishment of places of worship, evangelism, foreign aid, interfaith marriage, religious festivities, blasphemy, activity streams splinter and aspects of the non-religious influence, such as population density, the gap socioeconomic, implementation of education, ideological and regional political infiltration and international scale, which entered Indonesia through religious activities. This article examines these issues in the context of Indonesia.